Strategi Guru Partisipasi Anggota Terhadap Majlis Taklim Pada Masa New-Normal Di Jorong Batang Gunung Kec. Lembah Melintang Nagari Ujunggading Kab. Pasaman Barat - Reni, Yusma; Hasibuan , Pendi; Charles, Charles; M, Iswantir (Indonesian Research Journal on Education, 2023)
The background of this research is as we know that participation is the participation of a person or group of community members in an activity. Participation of members in the majlis taklim is very much needed to make a program successful and run according to the goals that have been set, both the participation of members in planning, implementing, and evaluating. However, during this new normal period, some members did notparticipate much in the majlis taklim that had been held, unlike the case before the new normal. In writing this thesis the type of research used is field research. The method of data collection is observation, interviews, and documentation. There are two types of information in this research, namely key informants and supportinginformants. , and the supporting informants are the majlis taklim officials. Based on the results of the research conducted, it is known that the participation of members in the majlis taklim during the new normal period is still relatively low, in contrast to the period before the New Normal. This can be seen from the forms of member participation, be it from planning, implementing, evaluating, monitoring, and supervising the Taklim Majlis, such as attendance or involvement participation, funding participation, staff participation, opinion sharing participation, monitoring participation, motivational participation is still low, not all members activelyparticipate in the activities of the taklim assembly. And the inhibiting factors for member participation in this taklim assembly are economic factors, and work factors, economic factors, educational factors, age factors, length of stay factors. This is seen from the results of observations and interviews that the author did.